Idealization XIV : models in science - Barbone, Giacomo, 1981- (Poznań Studies in the Philosophy of the Sciences and the Humanities, 2016)
Idealization XIV: Models in Science offers a detailed ontological, epistemological and historical account of the role of models in scientific practice. The volume contains contributions of different international scholars who developed many aspects of the use of idealizations and models both in the natural and the social sciences. This volume is particularly relevant because it offers original contributions concerning one of the main topic in philosophy of science: the role of models in such branches of the sciences and the humanities like comparative historical sociology, economics, history, linguistics and political philosophy. Contributors are: Giacomo Borbone, Krzysztof Brzechczyn, Mieszko Ciesielski, Adam Czerniak, Xavier de Donato Rodríguez, José L. Falguera, Adolfo García de la Sienra, Lidia Godek, Igor Hanzel, Łukasz Hardt, Krzysztof Kiedrowski, Barbara Konat, Zenonas Norkus, Piotr Przybysz, Piotr Szwochert